2015
DOI: 10.1016/j.sajb.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for “gibberellin-like” activity of coumarin

Abstract: The existing body of information defines some regulatory functions to secondary metabolites like coumarin (COU). Experience and some experimental results in our laboratory tempted us to test a GA-like activity of COU. Experiments were conducted with endospermic (de-embryonated) and embryonic wheat half grains treated with different concentrations of COU, for different time courses, alone or in combination with the GAbiosynthesis inhibitor paclobutrazol (P). Results showed that treatment with COU caused stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Similarly, Prabodh et al [43] and Khanh et al [44] observed that higher concentrations of template coumarin (above of 350 µM) were needed to reach 50% inhibition of Lactuca sativa , Lolium perenne and E. crus-galli germination process. Comparable results were also observed by Saleh and Abu El-Soud [45] on wheat germination. Also, other natural coumarins isolated from Meliaceae and Rutaceae, such as psoralen, showed lowest phytotoxic activity on germination process causing the complete inhibition at 1mM concentrations [46].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, Prabodh et al [43] and Khanh et al [44] observed that higher concentrations of template coumarin (above of 350 µM) were needed to reach 50% inhibition of Lactuca sativa , Lolium perenne and E. crus-galli germination process. Comparable results were also observed by Saleh and Abu El-Soud [45] on wheat germination. Also, other natural coumarins isolated from Meliaceae and Rutaceae, such as psoralen, showed lowest phytotoxic activity on germination process causing the complete inhibition at 1mM concentrations [46].…”
Section: Discussionsupporting
confidence: 85%
“…All the synthetic molecules strongly affected the root system more than the natural coumarins [45,46] inducing modifications on root morphology and anatomy, such as unaligned cells, gravitropism loss and root hair inhibition. Similar results were observed by several authors in treated roots with oryzalin, taxol and colchicines, affecting microtubule organization [63,64,65], which could also justify root hair loss [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…The production of hydrolytic enzymes excreted by the aleurone and scutellum layers is triggered by gibberellins, hormones produced in the scutellum and transported to the aleurone cells (reviewed by Yamaguchi, 2008;Sponsel, 2016). In wheat for example, the phenolic specialized metabolite coumarin has been shown to induce production of hydrolytic enzymes in aleurone cells (Saleh and Abu El-Soud, 2015). Tissue-wise localization of compounds during early germination and seedling development may, therefore, lend clues to their significance and biological activity.…”
mentioning
confidence: 99%
“…COU has a strong antioxidant nature, which may regulate plant growth by showing effective antioxidant capacity ( Parvin et al, 2021 ). COU also possess gibberellin-like activity and can stimulate amylase biosynthesis in germinating seeds (of wheat) and increase stem length in pea seedlings by inhibiting paclobutrazol (a GA inhibitor) activity ( Saleh et al, 2015 ; Saleh and El-Soud, 2015 ).…”
Section: Discussionmentioning
confidence: 99%